2014
DOI: 10.1016/j.jpubeco.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Smoking bans, maternal smoking and birth outcomes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 35 publications
5
85
0
1
Order By: Relevance
“…Other studies based on natural experiments or sibling comparisons have also found that smoking has a negative impact on newborn health and that this does not simply reflect other adverse circumstances affecting mothers who happen to smoke (1416). For example, researchers using data from 1.5 million births in New Jersey between 1989 and 2003 compared the birth weights of sibling pairs in which the mother smoked during one pregnancy but not the other.…”
Section: Prenatal Conditions and Offspring Outcomesmentioning
confidence: 99%
“…Other studies based on natural experiments or sibling comparisons have also found that smoking has a negative impact on newborn health and that this does not simply reflect other adverse circumstances affecting mothers who happen to smoke (1416). For example, researchers using data from 1.5 million births in New Jersey between 1989 and 2003 compared the birth weights of sibling pairs in which the mother smoked during one pregnancy but not the other.…”
Section: Prenatal Conditions and Offspring Outcomesmentioning
confidence: 99%
“…The 295 districts (Landkreise) constitute the upper-level local governments and roughly correspond with US counties in terms of population. Districts are mainly responsible 5 Most public economics studies using the synthetic control method evaluate regulations of tobacco (Abadie et al 2010, Bharadwaj et al 2014) and alcohol (Marcus and Siedler 2015).…”
Section: Districts In Germanymentioning
confidence: 99%
“…152 There is a limited body of research that suggests paradoxical effects can result from tobacco control measures due to compensatory smoking behaviors such as substituting behaviors (displacement of smoking from public places to private spaces, such as from work to home) and/or increased smoking intensity (extracting more nicotine per cigarette). [153][154][155] Although these paradoxical findings have not been universally supported by the research, 156 they raise concerns about potentially increased SHS exposure of children in these "private spaces" (home and private vehicles). This potential increase in SHS exposure further heightens the need to pursue options that promote smokefree environments for children.…”
Section: Beginning the Smokefree Movementmentioning
confidence: 98%